2006
DOI: 10.1104/pp.106.085597
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Stress Induction of the Gene Encoding Common Bean Acetyl-Coenzyme A Carboxylase

Abstract: Regulation of the cytosolic acetyl-coenzyme A carboxylase (ACCase) gene promoter from common bean (Phaseolus vulgaris) was studied in transgenic Arabidopsis (Arabidopsis thaliana) plants using a β-glucuronidase (GUS) reporter gene fusion (PvACCase∷GUS). Under normal growth conditions, GUS was expressed in hydathodes, stipules, trichome bases, flowers, pollen, and embryos. In roots, expression was observed in the tip, elongation zone, hypocotyl-root transition zone, and lateral root primordia. The PvACCase prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 69 publications
(81 reference statements)
1
18
0
Order By: Relevance
“…In recent years, several studies have shown that GUS expressions driven by the promoters of the genes, WOX3, cation-Cl -cotransporter (ccc), DR5, PvACCase, and AtSUC3, were in the same tissues including stipules, leaf hydathodes, leaf apex, root tips, lateral root buds, and anthers [29][30][31][32][33][34]. Several of the genes have also been demonstrated to function in the regulation of free auxin distribution in these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have shown that GUS expressions driven by the promoters of the genes, WOX3, cation-Cl -cotransporter (ccc), DR5, PvACCase, and AtSUC3, were in the same tissues including stipules, leaf hydathodes, leaf apex, root tips, lateral root buds, and anthers [29][30][31][32][33][34]. Several of the genes have also been demonstrated to function in the regulation of free auxin distribution in these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme plays an important role in controlling germination efficiency, i.e. seed vigour because: (1) ACCase plays a key regulatory role that catalyses the first committed step in lipid biosynthesis (Post-Beittenmiller et al 1993;Gornicki et al 1994;Sasaki and Nagano 2004) that is essential for resumption of embryonic growth and (2) by an alternative route ACCase drives the secondary biosynthetic pathway for flavonoids (Figueroa-Balderas et al 2006) that function as sun screen (Lois and Buchanan 1994;Landry et al 1995) and also as (nonenzymatic) ROS scavenging antioxidant (Yamasaki et al 1997); remaining un-degraded through structural activity relationship (Amic et al 2003) under (seed storage) stress conditions. It is thus conceivable that flavonoids serve to protect dry seed from maturation through storage to the germination stage (on imbibition).…”
Section: Re Cut Of the Hv-specific (Hvac 19) Fragment From Hv Varietiesmentioning
confidence: 99%
“…Among them, both cytosolic acetyl-CoA carboxylase (Acc-2) (Xscszm17 -FJ436983.1; Xscszm18 -EU660895.1) and plastid acetyl-CoA carboxylase (Acc-1) (Xscszm49 -EU660897.1) constitute an important element of plant response to various kinds of stresses, including nutrition. Acetyl-CoA carboxylase (ACCase; EC 6.4.1.2) catalyzes the ATP-dependent formation of malonyl-CoA from acetyl-CoA and bicarbonate (Figueroa-Balderas et al 2006). Malonyl-CoA is essential for fatty acid synthesis which occurs in plastids (Harwood, 1988).…”
Section: Discussionmentioning
confidence: 99%